Analisis Analysis of the Variety and Function of Uslub Jinas in the Qur'an Surah Yusuf - Thoriq, Rizka (Al-Fikrah, 2025)
The beauty of language is one of the miracles of the Qur'an that will not be timeless, still full of charm in terms of words and meaning. The language of the Qur'an will always be interesting to study, one of the language studies on the aspect of the beauty of the word is jinas. Jinas are two pronunciations that are similar in four ways, namely; letters, syakal (harakat), the number of letters and the order. This research aims to uncover the muhassinat lafdziyah form of jinas in the Qur'an surah yusuf. This study uses a qualitative approach and the type of research is literature, namely the object of the study prioritizes the study of literature in the form of books as a source of data. In this study, it explains the material about jinas and reveals the beauty of reciting in the form of jinas in surah Yusuf. The results of this study revealed that the pronunciation of jinas in surah yusuf is as many as 30 forms of jinas.